Poznanie i wolna wola – dwie podstawowe kategorie antropologii Ambrozjastra - Babiarz, Grzegorz (Vox Patrum, 2015)
Ambrosiaster belongs to the Roman school of exegesis. He deserves the attention because of the relations between him and Marius Victorinus, his predecessor, as well as Pelagius and Augustine, his successors. The purpose of the article was to present Ambrosiaster’s anthropology on the basis of his writings. The conclusions have been presented in three parts: the elements of human nature, the rationality of knowledge and the scope of free will. The first part shows the process in which the elements of nature are integrated. The spirit plays the decisive role synchronizing both the body and the soul. This dynamic and ongoing process is inspired by the presence of the Holy Spirit. The second part reveals two conditions for gaining knowledge: accepting the limitations of the mind and expanding and developing the principle of analogy. The last part presents two ways the free will is practised: by increasing how much one owns, which may be associated with lust, or by strengthening one’s inner strength. The role of the cultural and the ecclesial environment constitutes important information for the reconstruction of the views of Ambrosiaster. This raises the question whether – alongside Antioch and Alexandria – one could also talk about the Roman school of exegesis (Marius Victorinus, Ambrosiaster, Pelagius).